Effects of caffeine supplementation on exercise performance in volleyball players: A systematic review and meta-analysis - Chen, B.; Zhang, C.; Xu, Z.; Li, Y.; Guo, L.; Cao, Y.; Girard, O. (Nutrients, 2025)
Background/Objectives: The ergogenic effects of caffeine in team sports, particularly volleyball, have received significant research attention. This study sought to examine the effects of caffeine on both volleyball-specific and general performance outcomes.